Вы находитесь на странице: 1из 8

2011

I.
1. x = x + 1 .
2010 2011
: 2010 2011 .
1. x x = 2011k + d , d = 0, 1, , 2010 .
k + 1 . x ,

k + 1 x < k + 2 . x,
2010

2010k + 2010 2011k + d < 2010k + 4020 , 2010 k + d < 4020


2010 k + d 4019 . , 2011 d 2010
k = 2010 d , 2011 d , , 4019 d , , x = 2011k + d
, .
2. 2 log 3 (ctg x) = log 2 (cos x) .
:

{3 + 2 k

}.

2.
cos x > 0,
1)
(*)
ctg x > 0.
2) 2 log 3 (ctg x) = log 2 (cos x) log 3 (ctg x) = log 4 (cos x) .

(3)

t
log 3 (ctg x) = log 4 (cos x) = t , cos x = 4t , ctg x = 3t , sin x = 4 ,

(3)
(3)
2t
+ ( 4 ) = 1 . t = 1 , cos x = 1
2
2
3

2t
2t
42t + 4
= 1 . y = 42t + 4
,

42t

, (*), x = + 2 k , k .
3

( 2). , x = / 3 + 2n
. , .

(cos x ) 2 = sin x . log 2 3 < 1 ,


,
(2n; / 2 + 2n ) , .
, .
1log

3. a > 0, b > 0, c > 0 a + b + c = 1 . , a bc + bca + c ab 3 .


a +bc

b + ca

c + ab

3.

a bc + b ac + c ab = a +bc 2bc + b+ ac 2 ac + c + ab 2 ab ,

a +bc

b + ac

c + ab

a +bc

b + ac
c + ab
4 bc + ac + ab 3 .
a + bc b + ac c + ab

(*)

a + b + c = 1 , a + bc = a ( a + b + c ) + bc = ( a + b)( a + c ) .
, b + ac = ( a + b)(b + c ) c + ab = ( a + c )(b + c ) . (*)
, 4 ( ab(a + b) + bc(b + c) + ac(a + c) ) 3(a + b)(b + c)(c + a ) ,
, ,
a 2 b + ab 2 + b 2 c + bc 2 + a 2 c + ac 2 6abc .

(b a) (c b) (c a)

abc > 0 , a + b + b + c + a + c 6 .

4. ,
.
,
, r1 r2 .
: S =

r r r r
r1 r2 ( r1 + r2 )
S = 1 2 1 2 .
r1 + r2
r1 r2

4.) ,
, .

r1 = r2
,
,
, .
, r1 > r2 .
1 . .

ABC
(. .1). BC AC
a b ,
A
AB c. r2
O
1
, , r1
,
r1
O2
r2
a + c b = 2S ,
r1

, b = S 1 1 .
C
B

r2 r1
2
S
Puc.1
a + b + c = r ,

2
, , r2 = 12 ( a + b c )

r1 = 12 (b + c a ) , b = r1 + r2 S =

r1 r2 ( r1 + r2 )
.
r1 r2

2 . .

(. .2).
a + b c = 2 S
r1

, a = S 1 + 1

r2 r1
S
2
a + c b = r
2

1
r1 = 2 ( a + b + c )
, a = r1 r2 . ,

1
r2 = 2 (b + c a )

S=

r1 r2 ( r1 r2 )
.
r1 + r2

O1

E
A

r1

O2
r2

B C
Puc.2

4 : S = pr , S = ( p a )ra , CD = CE = p

(..2). S , p = a +b+c , r
2

, ra , a .

5. n , n 4 + 64n
.
: n .
5. , :

x4 + 4 y 4 = x2 + 2 y 2

( 2 xy ) = x 2 2 xy + 2 y 2

)( x2 + 2 xy + 2 y2 )

x y , , x 2 2 xy + 2 y 2 = ( x y ) 2 + y 2 ,
1 , x = y = 1 . ,
x 4 + 4 y 4 .
, n 4 + 64 n , n .
64 n = 64 84 k = 4 (2 8k ) . x = n y = 2 8k ,
x 4 + 4 y 4 . y 2 , .
4

6. ,
a b, . .
:

2ab
.
4

ABCD
6.
BC = a ,
AD = b

AB = AC = BD = CD = x .
, , A
, x = a + b . K

M
O

C
K

M BC AD .
B
ADK BMC BC AD
, , , , ,
,
KM ADK BMC. :
R = MO = 1

MB 2 BK 2 = 1

( a + b)2 b 2 a 2
BD 2 DM 2 BK 2 = 1

= 2ab .
2

7. f (x ) f ( x + 1) = f ( x)
x.
1

) ,

f ( x + 0,5)
dx 1 .
f ( x)

) ,

f ( x + )
dx 1 .
f ( x)

7.
1

a)

f ( x + 0,5)
dx =
f ( x)

0,5

f ( x + 0,5)
dx +
f ( x)
0,5

0,5

f ( x + 0,5)
dx +
f ( x)

f ( x + 0,5)
dx =
f ( x)
0,5

0,5

f ( x)
dx
f ( x + 0,5)

f ( x + 0,5)
dx +
f ( x)

0,5

f (u +1)
du =
f (u + 0,5)

0,5

2dx = 1

f ( x 0,5) = f ( x + 0,5) a + b 2 .
b

) : .
= 1 , n . [0;1]
n

k 1 ; k , k = 1,2, , n ,
n n
u = x k 1 .
n

0; 1 .
n

n
f (u + k )
n)
n
du =
du . , ,

k
k

1
1
f
u
+
f
u
+
k =1 0 (
0 k =1 (
n )
n )
f ( u + 1 ) f ( u + 2 ) f ( u + n )
n
n
n
n = n ,
, n
f (u ) f ( u + 1 ) f ( u + n 1 )
n
n
n

1
n

f u+k

1
n

f (u + 1) = f (u ) . , ,

1
n

n dx = 1 .
0

= m , . -, , f ( x + 1) = f ( x ) ,
n

, ,
,

) (

) (

f u + m f u + m +1 f u + n 1 f (u ) f u + m 1 ,
n

1. ,
, ,
, ,
, .
n , .
,
1

f ( x + n )
dx 1 . , ,
f ( x)

f ( x + n )
dx
f ( x)

f ( x + )
dx ,
f ( x)

. ,
n x [0;1]

f ( x + n ) f ( x + )

< , .
f ( x)
f ( x)

II.
8.

3 = 4x 5 .
log 2 x

: {2} .
. y = log 2 x , , y =

. ,
,

3 = 4x 5
log 2 x

3
log 2 x

y = 4 x 5 ,

x = 2 .
4

. , ,

y = log 2 x , , y = 3
log 2 x

, .. (0;1)
(1;+) . ,
. x = 2 x = 1 .
2

9. 100
15 . p% , 10%
. ?
: 50 50, 20 80, 10 90.
. x , y
.
x = 500 ,
p 10
x + y = 100,

15 < p < 100 .


100( p 15)
px + 10 y = 1500
y = p 10 ,

x , p500
, ,
10
p 10 500. :
p

20

50

50

35

20

80

60

10

90

. ,
x px , p
. .
10. AB ABC ABDE
, ABC.
, ,
BC = a , AC = b .
: a + b .
2

10.
1. ,
C .
: A(b; 0) B(0; a) .
E ,
(), (a + b; b) , ,
M BE

a + b ; a + b . , CM = a + b .
2

M
B

a
C

2. M ABDE.
ACB = AMB = 90 , ACBM , ,
, : CM AB = BC AM + AC BM = a AB + b AB , CM = a + b .
2

3. ACB AMB , M C
, AB .
ACM :

MC = 2 R sin BAC + 45

) = AB(sin BAC cos 45 + cos BAC sin 45) =

a D b
b
= a 2 + b2 a 2 +
2 = a +b .
2
2
2
2
2
2
2
a +b
a +b

4. , b
.
M
, M B
. , CM a
, a + b .
2
C
a
b A
3
x
x
11. 27 7 7 3 + 6 = 6 .
: {1} .
11.
y = 3 x , y 3 73 7 y + 6 = 6 .

E
b

1. z = 3 7 y + 6
y 3 = 7 z + 6,
3
z = 7 y + 6.
, , y 3 z 3 = 7( z y ) , y = z ,

y 2 + yz + z 2 0 . y 3 7 y 6 = 0 ,
y = 1; 2; 3 . , 3 x = 3 , x = 1 .
3
2. f ( x) = x 6 . g (x )

g ( x ) = 7 x + 6 . , y 3 73 7 y + 6 = 6
3

f ( y ) = g ( y ) , f ( f ( y ) ) = y . f ( x ) , ,
, f ( f ( y ) ) = y f ( y ) = y .
, .
3. y 3 7 3 7 y + 6 6 = 0 y > 0 .
, 0 < y 2 ,
( y 3 8, 7 3 7 y + 6 + 6 > 8) .

(y

7 3 7 y + 6 6 = 3y2

7
3 (7 y + 6)2
3

. ,

y > 2 . , f ( y ) = y 3 7 3 7 y + 6 6
y > 2 , .
: y = 3 , x = 1 .
12. P > 4 R , P , R
.
12.
1. 2R. ,
P > 4R (.. ).

ABC c
P R.
D
DBC. ACB < 90 , , CA
BD M (. ).
, ABC C
DBC AB + AC > DB + DC .
(*)

A
M

DMC AMB , DM = MC = DC = k < 1 .


MA

MB

AB

(*) AB + AM + MC > DM + MB + DC AB + AM + kMB > kAM + MB + kAB


(1 k ) AB + (1 k ) AM > (1 k ) MB AB + AM > MB , .
2. ABC
c P R,
A B < C . O ,
ABC, AD ,
BK CM , B C AD
. ABC ,
, AD B F
(. ).
BAD < BAC < ACB CAD < BAC < ABC ,

A
O

BD < AB CD < AC . , K M OD, ,


, AK > R AM > R . , BK CM
OBK OCM , R, BK < R
CM < R . , BK < AK CM < AM .
BK ABD, BK 2 = AK KD ,
BK < AK , BK > KD , , , AB + BF > AB + BK > AK + KD = 2 R .
ACD, CM 2 = AM MD , CM > MD ,
AC + CF > AC + CM > AM + MD = 2 R .
, P = AB + BC + AC = ( AB + BF ) + ( FC + AC ) > 2 R + 2 R = 4 R .
, B = C , F, K M ,
.
3 4. P = a + b + c = 2 R ( sin + sin + sin ) , , ,

, , sin + sin + sin > 2 .


1.

y = sin x 0; (0; 0 )
2

(2 )

( 2)

; 1 . y = 2 x . , x 0;

sin x > 2 x .

sin

> 2 , sin > 2

, sin

> 2 ,

+ + = .

2.
sin + sin + sin = 2sin

+
2

cos

+ 2sin cos = 2cos

< , ( < < + ), (*) > 2cos


2

(cos

(cos

+ sin

+ sin

).

(*)

) = 1 + cos + sin .

, cos + sin > cos 2 + sin 2 = 1 .


7